Pengaruh Kepercayaan Investor dan Struktur Modal terhadap Kinerja Keuangan di Masa Pandemi Covid-19 - Tasya Aprilia; Sri Fadilah (UNISBA Press, 2022)
Abstract. This study aims to determine the effect of investor confidence and capital structure on financial performance during the Covid-19 pandemic in the construction and building sub-sector industries listed on the Indonesia Stock Exchange in Quarter II-IV of 2020. The object of this research is Investor Confidence, Capital Structure and Financial Performance, while the subject in this study is the Construction and Building Sub-Sector Industry Listed on the Indonesia Stock Exchange Quarter II-IV 2020. This research method is quantitative with a descriptive and verification approach. In this study using secondary data with a population of 17, namely the Construction and Building Sub-Sector Industry Listed on the Indonesia Stock Exchange and a sample of 51. Hypothesis testing using multiple linear regression analysis, classical assumption analysis, coefficient of determination analysis, and hypothesis testing using the F test. and t test. Based on the results of research on partial hypothesis testing or t test, it is explained that Investor Confidence has no significant effect on Financial Performance, then Capital Structure has a significant effect on Financial Performance. Simultaneously explained that Investor Confidence and Capital Structure have a significant effect on Financial Performance. Investor Confidence and Capital Structure have an effect of 14.2% on Financial Performance Abstrak. Penelitian ini bertujuan untuk mengetahui Pengaruh Pengaruh Kepercayaan Investor dan Struktur Modal Terhadap Kinerja Keuangan Di Masa Pandemi Covid-19 Pada Industri Sub Sektor Konstruksi Dan Bangunan Yang Terdaftar Di Bursa Efek Indonesia Triwulan II-IV Tahun 2020. Objek penelitian dalam penelitan ini adalah Kepercayaan Investor, Struktur Modal dan Kinerja Keuangan, sedangkan subjek dalam penelitian ini adalah Industri Sub Sektor Konstruksi Dan Bangunan Yang Terdaftar Di Bursa Efek Indonesia Triwulan II-IV tahun 2020. Metode penelitian ini adalah kuantitatif dengan pendekatan deskriptif dan verifikatif. Dalam penelitian ini menggunakan data sekunder dengan populasi sebanyak 17 adalah Industri Sub Sektor Konstruksi Dan Bangunan Yang Terdaftar Di Bursa Efek Indonesia serta sampel sebanyak 51. Pengujian hipotesis menggunakan analisis regresi linier berganda, analisis asumsi klasik, analisis koefisien determinasi, serta uji hipotesis menggunakan uji F dan uji t. Berdasarkan hasil penelitian pada uji hipotesis secara parsial atau uji t menjelaskan bahwa Kepercayaan Investor tidak berpengaruh signifikan terhadap Kinerja Keuangan, kemudian Struktur Modal berpengaruh signifikan terhadap Kinerja Keuangan. Secara simultan menjelaskan bahwa Kepercayaan Investor dan Struktur Modal berpengaruh signifikan terhadap Kinerja Keuangan. Kepercayaan Investor dan Struktur Modal memberikan pengaruh sebesar 14.2% terhadap Kinerja Keuangan